Antioxidant activity and phytochemical components of Jatropha curcas Linn. root extract (Journal of Biochemistry, Microbiology and Biotechnology, 2017)
Jatropha curcas Linn. is a multipurpose plant in the Euphorbiaceae family. Numerous reportshave indicated the antioxidant properties of phenolics and flavonoids present in J. curcas rootmethanolic extract. In the present study, 80% methanolic extract of J. curcas root was preparedand used for extraction of bioactive compounds with five solvents (hexane, chloroform, ethylacetate, n-butanol and water) by liquid-liquid fractionation. The fractions were evaluated fortotal phenolic content (TPC), total flavonoid content (TFC) and antioxidant activities by usingthe 2-2’-diphenyl-1-picrylhydrazyl (DPPH), ferric reducing/antioxidant potential (FRAP) and2,2′-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid (ABTS) assays. The phytochemicalcompounds present in each fraction were identified by liquid chromatography mass spectrometry(LCMS) analysis. The TPC of ethyl acetate and n-butanol fractions were 34.0 ± 0.02 μg GAE/gDW and 33.1± 0.01 μg GAE /g DW, respectively, while the TFC were 9.2 ± 0.04 μg CE/g DWand 10.1 ± 0.01 μg CE/g DW, respectively. The free radical scavenging activity varied with thesolvents used. Ethyl acetate fraction showed the highest inhibition for DPPH (48.7%) and FRAP(79.6%) assays, while n-butanol fraction showed the highest ABTS radical scavenging activity(94.8%). The LCMS analysis showed the compounds present in the various fractions werephenolic and flavonoid derivatives such as coumaric acid, epigenin, quercetin, leuteolin and pcoumaroylquinicacid. The results showed that TPC, TFC and antioxidant activity for ethylacetate and n-butanol fractions were higher compared to the other solvent fractions.
Keywords: Jatropha curcas Linn. root; solvent fractions; phenolics; flavonoids; antioxidant activity